Ruta Condor (Route of the Condor) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The project aimed at restoring and conserving the genetic diversity of native potatoes in situ – high in the Andes, where the crops originated. Scientists, farmers, and local partners repatriated over 4,600 samples of more than 1,200 varieties of native potato in 41 locations, following the ancient north south pre-Columbian route that unified the Inca Empire. Cultivation of various varieties by numerous families is done using the 'potato park' model.